Herbal Contraceptives: A Conventional Birth Control Method (International Journal of Scientific Research in Science and Technology, 2024)
One of the main strategies that appears to be successful in population management is human fertility control. Numerous potential techniques, such as hormonal and pharmacological ones, have been used to cause infertility. Because of their apparent safety, cost, and accessibility, herbal contraceptives have attracted growing interest as supplemental or alternative birth control techniques. The scientific evidence pertaining to several plant-based contraceptive drugs is reviewed in this review study, which also looks at their safety profiles, modes of action, efficacy, and possible adverse effects. Many plant species are said to have contraceptive qualities, and herbal treatments have long been used in traditional medical systems across various cultures to regulate reproduction. Among the mechanisms of action studied are uterine contractility regulation, spermatogenesis disruption, ovulation inhibition, and hormonal modulation. The paper also discusses herbal formulations, dose accuracy, and potential herb-drug interactions. It also highlights the necessity of conducting more thorough research, such as randomized controlled trials, in order to more accurately determine whether herbal contraceptives are a viable ainstream choice. This study seeks to present a fair assessment of the state of herbal contraception today and encourage more research into their potential as affordable, sustainable family planning options, especially in environments with limited resources.